Analysis of the Use of the CHRONOS Online Slot Time Application in Issuing ATC Clearance at Soekarno-Hatta International Airport - Triyono Yuniarto; Dwi Lestary; Yudha Abimanyu (CV. AFDIFAL MAJU BERKAH, 2026)
This research aims to analyze the implementation of the CHRONOS Online Slot Time Application in supporting the issuance of Air Traffic Control (ATC) clearance at Soekarno-Hatta International Airport. The study investigates how CHRONOS contributes to improving efficiency in flight scheduling, reducing clearance delays, and identifying technical and operational challenges during peak traffic hours. The research employs a qualitative descriptive method, involving observations, semi-structured interviews, and document studies with key personnel from Clearance Delivery (CD), Aeronautical Reporting Office (ARO), and Air Traffic Flow Management (ATFM) units at Jakarta Air Traffic Service Center (JATSC). The findings indicate that CHRONOS functions effectively at the slot approval stage, but integration issues between CHRONOS and the ATS system hinder real-time data synchronization. Consequently, manual coordination between CD, ARO, and ATFM remains necessary, leading to increased workload and clearance delays when slot times expire. Moreover, discrepancies between approved slot times and system updates cause pushback delays, congestion at aprons, and reduced operational efficiency. The study concludes that while CHRONOS enhances transparency and procedural consistency, further system integration, automated alerts, and improved inter-unit coordination are essential to optimize its performance. These results are expected to support the refinement of Standard Operating Procedures (SOPs) and the application of Collaborative Decision Making (CDM) in air traffic management operations.